Cross-Point Comparison of Multistage Non-Blocking Technologies - Zulfin, Muhammad; Suherman, S; Fauzi, Rahmad; Razali, M; Pinem, Maksum (International Journal of Engineering and Technology, 2018)
Multistage switching networks play important role in communication and computer network. They make communication nodes connect to each other. In computer hardware switches connect processors and memories. Initially, switches are arranged as one stage interconnection. As clients are growing, multistage is a must. The finding Clos multistage switching initiated multistage technologies. Benes improves Clos by reducing number of cross-points by using a 2 x 2 switch element and call re-routing. Batcher improves the technology by other way which is sorting destination address. Banyan is then joined to Batcher to simplify routing control. This paper analyses the number of cross-point required in Clos, Benes and Batcher Banyan to accomplish multistage switching architecture of 16, 64, 256, 1024 and 2048 input/output ports. As results, Clos cross-point is in averages 495.24% higher than Benes and 160.30% higher than Batcher Banyan. Clos blocking probabilities are closed to zero. Benes blocking probabilities are conditionally zero. Batcher Banyan blocking probabilities are zero.Â Â
Keywords: Multistage switching; Clos; Benes; Batcher Banyan; Cross-points